Effect of scan mode and focal spot size in airway dimension measurements for ultra-high-resolution computed tomography of chronic obstructive pulmonary disease: A COPDGene phantom study. (February 2020) - Mikayama, Ryoji; Shirasaka, Takashi; Yabuuchi, Hidetake; Sakai, Yuki; Kojima, Tsukasa; Kondo, Masatoshi; Yoshikawa, Hideki; Kato, Toyoyuki
Highlights: UHRCT using the super high resolution (SHR) mode could improve measurement accuracy. The small focal spot contributed to an accurate evaluation of a small airway. There is a high inter- and intra-observer variability of airway measurement in SHR. Abstract: Purpose: Quantitative evaluations of airway dimensions through computed tomography (CT) have revealed a good correlation with airflow limitation in chronic obstructive pulmonary disease. However, large inaccuracies have been known to occur in CT airway measurements. Ultra-high-resolution CT (UHRCT) might improve measurement accuracy using precise scan modes with minimal focal spot. We assessed the effects of scan mode and focal spot size on airway measurements in UHRCT. Methods: COPDGene Ⅱ phantom, comprising a plastic tube mimicking human airway of inner diameter 3 mm, wall thickness 0.6 mm, and inclination 30 degrees was scanned at super high resolution (SHR, beam collimation of 0.25 mm × 160 rows) and high resolution (HR, beam collimation of 0.5 mm × 80 rows) modes using UHRCT. Each acquisition was performed both with small (0.4 × 0.5 mm) and large (0.6 × 1.3 mm) focal spots. The wall area percentage (WA%) was calculated as the percentage of total airway area occupied by the airway wall. Statistical analysis was performed to compare the WA% measurement errors for each scan mode and focal spot size. Results: The WA% measurement errors in the SHR mode were 9.8% with a small focal spot and 18.8% with a large one. The measurement errors in the HR mode were 13.3% with a small focal spot and 21.4% with a large one. There were significant differences between each scan mode and focal spot size ( p < 0.05). Conclusions: The SHR mode with a small focal spot could improve airway measurement accuracy of UHRCT.